Policy of Information and Communication Technologies to Promote the Formation of Future Business Models - Velinda Febriana; Eko Purwanto (LPPM Universitas Duta Bangsa Surakarta, 2021)
ICT industry becomes a driver of change, many sectors that can change not only from the telecommunications sector. ICT developments are spurring the digital economy enables sectors that had previously been in the safe zone, being threatened because of the presence of substitute industry that has begun to emerge. Trend to date, some companies use Internet-based applications to support the marketing of their products. Not only on the promotional activities featuring products that are known by consumers, even some companies use Internet technology to support transactions, such as the sale of products to consumers. Innovation and competition to push toward creative destruction, there is a long lost services and value added is replaced by the presence of ICT innovation. The government must be present and ready to anticipate the changes that may occur due to the development of ICT, which grew rapidly at the policy level. The study is qualitative and done through the study of literature and focused discussions involving experts and stakeholders concerned. the results of this study are as advice on policy will be taken by the government to the ICT industry sector forward in the face of the rapid innovation of ICT.